There is another way: The faculty-developed Idaho Comprehensive Literacy Assessment for K-8 pre-service teachers - Squires, David; Canney, George F.; Trevisan, Michael S. (Education Policy Analysis Archives, 2004)
In this era of external teacher testing with the intent of ensuring the competence of the teaching force, as well as holding students and institutions accountable for results, the Idaho Comprehensive Literacy Assessment (ICLA) stands in sharp contrast. It represents an alternative to external testing of preservice teachers, testing procured from an outside agency unconnected to preservice programs, since it has been developed and is managed by literacy faculty from Idaho’s major institutions of higher learning. This paper provides a brief history of major events in the field of literacy including teacher testing initiatives and policies, which led to the creation of the ICLA. A description of the ICLA assessment and its construction is provided, along with a report of initial performance. Implications and policy consequences of this approach are explored.